2022
DOI: 10.3390/healthcare10101972
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Intergroup Threats Perceived by Chinese Physicians and Its Association with Organizational Psychology, Behavior, and Well-Being during the COVID-19 Pandemic: A Cross-Sectional Survey

Abstract: (1) Background: Chinese physicians have encountered serious physical and verbal attacks in recent decades due to poor patient–physician relationships, leading to a broad spectrum of negative consequences. This study aims to assess the status of intergroup threats perceived by physicians and explore its association with organizational psychology, behavior, and well-being during the COVID-19 pandemic. (2) Methods: We conducted a cross-sectional online survey with physicians from November to December 2020 in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…What's more, it was found that high perceived stress was a risk factor of positive BI, meaning participants with higher perceived stress would exhibit less positive BI. This was consistent with previous researches that stress was influencing factors of working turnover intention (Lu et al, 2017), home-gardening intentions (Wu et al, 2022), and defensive medical behavior (Sun et al, 2022). During the epidemic, people faced a variety of stressors, including fears of infection and inadequate supplies Just as supplementary material indicated, the stresses of older people mainly come from the overall stress, living provisions, risk of COVID-19 infection, family dysfunction, children learning online, medical or medicine demand, economic income, negative information, cramped space, and working at home.…”
Section: Discussionsupporting
confidence: 93%
“…What's more, it was found that high perceived stress was a risk factor of positive BI, meaning participants with higher perceived stress would exhibit less positive BI. This was consistent with previous researches that stress was influencing factors of working turnover intention (Lu et al, 2017), home-gardening intentions (Wu et al, 2022), and defensive medical behavior (Sun et al, 2022). During the epidemic, people faced a variety of stressors, including fears of infection and inadequate supplies Just as supplementary material indicated, the stresses of older people mainly come from the overall stress, living provisions, risk of COVID-19 infection, family dysfunction, children learning online, medical or medicine demand, economic income, negative information, cramped space, and working at home.…”
Section: Discussionsupporting
confidence: 93%